(untitled) (Impact: Journal of Transformation, 2018)
The quality of air is determined by the extent of atmospheric pollution. The USEPA identifies six criteria pollutants namely particulate matter (PM), ground level ozone, carbon monoxide, sulphur oxides, nitrogen oxides and lead exposure as toxic and injurious to human health. Thus, there is a need to examine ambient air quality and incidence of selected diseases in Lagos, Nigeria. The data for the study include a five-year sampling on criteria pollutants and data on selected airborne diseases that were collected for the same period of time. Data analysis adopted the use of multiple regression for examining the relationship between ambient criteria pollutants and the occurrence of diseases. GIS procedure was also employed to produce a map showing the spatial pattern of criteria pollutants. The findings reveal an R2 of 19.8, 13.9, 8.9, 8.4 and 16.8 percent respectively for asthma, bronchitis, heart failure, lung cancer and tuberculosis. The results show a low level of association and this was attributed to other causal factors responsible for the occurrence of the selected diseases. However, this study provides evidence of an association between outdoor air pollution and increased risk from these diseases. Therefore, the study recommends that governments, and other stakeholders in health sectors should harmonize efforts, resources and ideas towards effective planning, monitoring, policy implementation and provision of facilities that could control and ameliorate the presence of pollutants to which urban residents are exposed thereby reducing the health effects from such exposures.